Ответ:
(0,4928х + 0,03) - 0,4828х= 0,4928х+0,03-0,4828х= 0,01х+0,03
Если х=0,17, то 0,01*0,17+0,03=0,0017+0,03=0,0317
Если х=100, то 0,01*100+0,03=1+0,03=1,03
Если х=0,01, то 0,01*0,01+0,03=0,0001+0,03=0,0301
1. 0,0317 если х = 0,17
2. 1,03 если х = 100
3. 0,0301 если х = 0,01
Пошаговое объяснение:
(0,4928х + 0,03) - 0,4828х = 0,4928х + 0,03 - 0,4828х = 0,01х + 0,03
1. 0,01х + 0,03 если х = 0,17
0,01х + 0,03 = 0,01 * 0,17 + 0,03 = 0,0017 + 0,03 = 0,0317
(0,4928х + 0,03 ) - 0,4828х = 0,4928х + 0,03 - 0,4828х = 0,01х + 0,03
2. 0,01х + 0,03 если х = 100
0,01х + 0,03 = 0,01 * 100 + 0,03 = 1 + 0,03 = 1,03
3. 0,01х + 0,03 если х = 0,01
0,01х + 0,03 = 0,01 * 0,01 + 0,03 = 0,0001 + 0,03 = 0,0301
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
(0,4928х + 0,03) - 0,4828х= 0,4928х+0,03-0,4828х= 0,01х+0,03
Если х=0,17, то 0,01*0,17+0,03=0,0017+0,03=0,0317
Если х=100, то 0,01*100+0,03=1+0,03=1,03
Если х=0,01, то 0,01*0,01+0,03=0,0001+0,03=0,0301
Ответ:
1. 0,0317 если х = 0,17
2. 1,03 если х = 100
3. 0,0301 если х = 0,01
Пошаговое объяснение:
(0,4928х + 0,03) - 0,4828х = 0,4928х + 0,03 - 0,4828х = 0,01х + 0,03
1. 0,01х + 0,03 если х = 0,17
0,01х + 0,03 = 0,01 * 0,17 + 0,03 = 0,0017 + 0,03 = 0,0317
(0,4928х + 0,03 ) - 0,4828х = 0,4928х + 0,03 - 0,4828х = 0,01х + 0,03
2. 0,01х + 0,03 если х = 100
0,01х + 0,03 = 0,01 * 100 + 0,03 = 1 + 0,03 = 1,03
3. 0,01х + 0,03 если х = 0,01
0,01х + 0,03 = 0,01 * 0,01 + 0,03 = 0,0001 + 0,03 = 0,0301